Automatic cortical representation of auditory pitch changes in Rett syndrome. Issue 1 (December 2016) - Foxe, John; Burke, Kelly; Andrade, Gizely; Djukic, Aleksandra; Frey, Hans-Peter; Molholm, Sophie
Abstract Background Over the typical course of Rett syndrome, initial language and communication abilities deteriorate dramatically between the ages of 1 and 4 years, and a majority of these children go on to lose all oral communication abilities. It becomes extremely difficult for clinicians and caretakers to accurately assess the level of preserved auditory functioning in these children, an issue of obvious clinical import. Non-invasive electrophysiological techniques allow for the interrogation of auditory cortical processing without the need for overt behavioral responses. In particular, the mismatch negativity (MMN) component of the auditory evoked potential (AEP) provides an excellent and robust dependent measure of change detection and auditory sensory memory. Here, we asked whether females with Rett syndrome would produce the MMN to occasional changes in pitch in a regularly occurring stream of auditory tones. Methods Fourteen girls with genetically confirmed Rett syndrome and 22 age-matched neurotypical controls participated (ages 3.9–21.1 years). High-density electrophysiological recordings from 64 scalp electrodes were made while participants passively listened to a regularly occurring stream of 503-Hz auditory tone pips that was occasionally (15 % of presentations) interrupted by a higher-pitched deviant tone of 996 Hz. The MMN was derived by subtracting the AEP to these deviants from the AEP produced to the standard. Results Despite clearly anomalous morphology and latency of the AEP to simple pure-tone inputs in Rett syndrome, the MMN response was evident in both neurotypicals and Rett patients. However, we found that the pitch-evoked MMN was both delayed and protracted in duration in Rett, pointing to slowing of auditory responsiveness. Conclusions The presence of the MMN in Rett patients suggests preserved abilities to process pitch changes in auditory sensory memory. This work represents a beginning step in an effort to comprehensively map the extent of auditory cortical functioning in Rett syndrome. These easily obtained objective brain measures of auditory processing have promise as biomarkers against which future therapeutic efforts can be assayed.